Downward finger displacement distinguishes Parkinson disease dementia from Alzheimer disease. (1st February 2018) - Lieberman, Abraham; Deep, Aman; Shi, Jiong; Dhall, Rohit; Shafer, Saulena; Moguel-Cobos, Guillermo; Dhillon, Ravneet; Frames, Christopher W.; McCauley, Margaret
ABSTRACT: Purpose/Aim of the study: To study finger displacement in patients with Parkinson disease dementia (PDD) and in patients with Alzheimer disease (AD). Methods: We examined 56 patients with PDD and 35 with AD. Patients were examined during their regular outpatient clinic visit. Finger displacement was measured by observers not actively involved in the study using a creative grid ruler for all PDD and AD patients. Finger displacement was examined by asking patients to point their index fingers toward the grid ruler with the nails facing upward. Patients were asked to maintain the pointing position for 15 s. After 15 s, patients were asked to close their eyes for another 15 s while maintaining the same position. A positive result was downward index finger displacement of ≥5 cm within the 15-second time window with eyes closed. Results: Of the 56 PDD patients, 53 had bilateral finger displacement of >5 cm. In comparison, of the 35 AD patients, only 1 patient had minimal displacement. Conclusions: Results of the non-invasive finger displacement test may provide insight, on an outpatient basis, of the integrity of subcortical–cortical circuits. Downward finger displacement, especially bilateral downward displacement, may signal the extensive disruption of subcortical–cortical circuits that occurs in PDD patients. Abbreviations: AChE: acetylcholinesterase; AD: Alzheimer disease; DLB: dementia with Lewy bodies; ET: essential tremor; MDS-UPDRS: Movement Disorder Society–sponsored Unified Parkinson's Disease Rating Scale; MMSE: Mini-Mental State Examination; PD: Parkinson disease; PDD: Parkinson disease dementia